Wastewater treatment using photocatalysis: Destruction of methylene blue dye from wastewater streams - Dennis P. Kumar,; Abdul Rahman Mohamed,; Subhash Bhatia, (2002)
Photocatalytic processes have been suggested as an alternative treatment for water pollutants. Although presently many treatment methods are being used, most of them do not completely destroy the pollutants but only offer phase transfer or partial degradation of the pollutants. In photocatalytic processes, a semiconductor photocatalyst is activated with ultraviolet (UV) irradiation. The activated photocatalyst promotes the formation of hydroxyl radicals, which in turn completely degrades the pollutants. In the present study, an ultraviolet irradiated photoreactor system was used to degrade methylene blue dye in aqueous solutions. The photocatalyst used was titanium dioxide (TiO2) Experiments were performed with varying catalyst loading, initial concentration of dye, circulation flow rate and air flow rate. Initial reaction rates of dye degradation were used to compare the effect of varying the above variables. The effect of increasing the catalyst loading from 0 to 0.4 wt% showed that an increase in the initial reaction rate, reaching an optimum at catalyst loading of 0.2 wt%. Effect of initial concentration has proven that lower initial concentration resulted in more efficient degradation of the dye. The increase in the initial reaction rate degradation with increasing circulation flow rate confirmed the significant role played by external mass transfer. Introduction of air to the system did not significantly increase in the initial reaction rate when the air flow rate was increased from 0 to 4.0 liter min-1